Detecção de Cryptosporidium serpentis em amostras fecais de serpentes utilizando PCR em tempo real - Silva, Deuvânia Carvalho da [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Cryptosporidium serpentis infection is common in reptiles, especially snakes, and is characterized by chronic infection with severe hypertrophic gastritis, which can be lethal. This research aimed to use the real- time polymerase chain reaction (PCR) targeting the heat shock protein gene (Hsp70) for detection of C. serpentis in fecal samples of 503 snakes, and to determine its analytical and epidemiological specificity and sensitivity using, as a gold standard, the nested PCR targeting the 18S rRNA (18S rRNA) gene followed by sequencing of the amplified fragments (nPCR/S). The real-time PCR was positive for C. serpentis in 17 samples (3.37%), and nPCR/S resulted in positive results for C. serpentis in 15 samples (2.98%). It was also observed that the nPCR/S was positive for Cryptosporidium spp. in 60 samples (11.98%). Sequencing of the fragments amplified by nPCR was possible in 38 samples, and resulted in the identification of Cryptosporidium tyzzeri, Cryptosporidium muris, Cryptosporidium varanii and C. serpentis in several species of snakes. The sensitivity and specificity of real-time PCR were, respectively, 93.8% and 99.5%. Although three samples were positive for C. serpentis only by real-time PCR, and were considered as false positive results in the estimation of the epidemiological specificity and sensitivity, the melting curve analysis indicated that these samples had the same melting temperature of the C. serpentis samples. Thus, we conclude that real-time PCR targeting the gene Hsp70 is a sensitive and specific method for the detection of C. serpentis in fecal samples from snakes
Keywords: Cryptosporidium; Diagnóstico molecular; Epidemiologia; Reptil; Cobra; Reação em cadeia de polimerase; Cryptosporidium serpentis